Comparison of simple and complex auditory‐visual conditional discrimination training. Issue 2 (25th April 2014) - Rosales, Rocío; Maderitz, Cecelia; Garcia, Yors A.
<x xml:space="preserve">Abstract</x> We investigated the relative effects of simple and complex auditory‐visual discrimination training using an adapted alternating treatments design to establish derived stimulus relations in 2 children who had been diagnosed with autism and 1 typically developing peer. Emergence of untrained conditional relations was observed after training in both conditions, with a possible advantage of simple‐sample training for 1 participant. Results of generalization and follow‐up probes were mixed.